2007
DOI: 10.1124/dmd.107.016840
|View full text |Cite
|
Sign up to set email alerts
|

Serine Hydroxymethyltransferase Isoforms Are Differentially Inhibited by Leucovorin: Characterization and Comparison of Recombinant Zebrafish Serine Hydroxymethyltransferases

Abstract: ABSTRACT:Serine hydroxymethyltransferase (SHMT) provides activated onecarbon units required for the biosynthesis of nucleotides, protein, and methyl group by converting serine and tetrahydrofolate to glycine and N 5 ,N 10 -methylenetetrahydrofolate. It is postulated that SHMT activity is associated with the development of methotrexate resistance and the in vivo activity of SHMT is regulated by the binding of N 5 -CHO-THF, the rescue agent in high-dose methotrexate chemotherapy. The aim of this study is to adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
1
24
0
1
Order By: Relevance
“…Using the zebrafish model for drug discovery is foreseen to significantly speed up the translation of drug or treatments from bench research to bedside reality by revolutionizing the cell-based assays to embryo-based screening (Kari et al, 2007). In previous studies, we have shown that zebrafish folate enzymes are comparable with their human and mammalian counterparts for their catalytic and structural properties, as well as susceptibility to antifolate compounds (Chang et al, 2006(Chang et al, , 2007Kao et al, 2008). This purified recombinant z␥GH will allow for further investigation to unravel the role of this key enzyme in regulating the intracellular availability of folates and antifolate drugs and to use zebrafish as an in vivo model for folate-related studies and antifolate drug discovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the zebrafish model for drug discovery is foreseen to significantly speed up the translation of drug or treatments from bench research to bedside reality by revolutionizing the cell-based assays to embryo-based screening (Kari et al, 2007). In previous studies, we have shown that zebrafish folate enzymes are comparable with their human and mammalian counterparts for their catalytic and structural properties, as well as susceptibility to antifolate compounds (Chang et al, 2006(Chang et al, , 2007Kao et al, 2008). This purified recombinant z␥GH will allow for further investigation to unravel the role of this key enzyme in regulating the intracellular availability of folates and antifolate drugs and to use zebrafish as an in vivo model for folate-related studies and antifolate drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…We had carefully examined the coding sequence for accuracy and codon usage and found several rarely used codons in E. coli. However, the use of the Rosetta strain for expression should have overcome this potential problem (Chang et al, 2007). We also tested for inclusion bodies and culture broth with SDS-PAGE for the possibility of aggregation or export of expressed z␥GH because secretion of this protein had been reported in mammalian tumor cell lines (Gourdon et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This "closed and isolated system" enables the intracellular fluctuation among different folate derivatives to be observed. Many zebrafish folate enzymes have been shown to be comparable to mammalian orthologs, supporting the appropriateness of modeling the impact of ethanol on folate-mediated OCM with zebrafish (7)(8)(9)(10)(11). Here, we report how the embryonic folate status and the expression of folate enzymes are altered when embryos are exposed to ethanol.…”
mentioning
confidence: 99%
“…For gene expression characterization and folate content measurement, ethanol was added to 3-hpf embryos for 6 h before mRNA extraction. For promoter activity assays in cells, zebrafish liver epithelium cells (ZLE) were cultured in Leibovitz's 15 medium supplemented with 10% FBS at 28°C as previously described (8). Cells were seeded (1 ϫ 10 6 cells/ 6-cm dish) and transfected with promoter constructs.…”
mentioning
confidence: 99%